Indonesian Coffee Exports in The Global Market and The Variables That Affect Them - Rahman, Rizky Mulia; Ridwan, Mochamad; Hadistyana Mutiarahmi (Program Studi Ekonomi Syariah, FEBI UIN Datokarama Palu, 2024)
The aim of this research is to analyse the situation of Indonesian coffee exports in the short and long term and the reasons why Indonesian coffee exports are able to compete in the global market. The data used in this research is secondary data in the form of numerical data with time series data type over a period of 72 months (January 2016 - December 2021). The analytical method used is the Error Correction Model (ECM) using the dependent variable the volume of Indonesian coffee exports and the independent variables, namely coffee production, exchange rate, inflation, international coffee prices and substitute prices. The research results show that there are no variables that significantly influence Indonesian coffee export volumes in the short term. In the long term, only coffee production has a significant positive effect, and the exchange rate has a significant negative effect, while the other variables have no significant effect. There are several reasons for the demand for coffee exported from Indonesia, namely the type, taste quality, aroma and uniqueness of the coffee produced in Indonesia.